2000
DOI: 10.1042/bj3470089
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6-induced STAT3 transactivation and Ser727 phosphorylation involves Vav, Rac-1 and the kinase SEK-1/MKK-4 as signal transduction components

Abstract: In the present study, signal transducer and activator of transcription 3 (STAT3) Ser(#( phosphorylation and transactivation was investigated in relation to activation of mitogen-activated protein (MAP) kinase family members including extracellularsignal-regulated protein kinase (ERK)-1, c-Jun N-terminal kinase (JNK)-1 and p38 (' reactivating kinase ') in response to interleukin (IL)-6 stimulation. Although IL-6 can activate ERK-1 in HepG2 cells, STAT3 transactivation and Ser(#( phosphorylation were not reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(21 citation statements)
references
References 52 publications
2
18
0
1
Order By: Relevance
“…7). This is in agreement with a study performed in HepG2 cells where IL-6 activated ERK1 and slightly p38 but not Jun N-teminal kinase-1 (JNK1) [34]. The residue within gp130 necessary for ERK activation was identified to be Tyr 759 [24].…”
Section: The Role Of Mapk and Pi3k/pkb In Il-6-dependent Ho-1 Regulationsupporting
confidence: 80%
See 1 more Smart Citation
“…7). This is in agreement with a study performed in HepG2 cells where IL-6 activated ERK1 and slightly p38 but not Jun N-teminal kinase-1 (JNK1) [34]. The residue within gp130 necessary for ERK activation was identified to be Tyr 759 [24].…”
Section: The Role Of Mapk and Pi3k/pkb In Il-6-dependent Ho-1 Regulationsupporting
confidence: 80%
“…[3][4][5] indicating that in addition to the Jak/STAT pathway, MAPK and PI3K/PKB cascades may also be involved in IL-6 signaling [15]. Moreover, several MAP kinases as well as PI3K were shown to contribute to STAT3 phosphorylation at Ser 727 [34,35]. In our study, IL-6 treatment led to phosphorylation of ERK1/2 and did not induce c-Jun or p38 MAPK phosphorylation in PHC (Fig.…”
Section: The Role Of Mapk and Pi3k/pkb In Il-6-dependent Ho-1 Regulationmentioning
confidence: 51%
“…Signal transducer and activator of transcription-3 (Stat3) is a latent cytoplasmic transcription factor that functions as an intracellular effector activated by various ligands including members of the interleukin-6 (IL-6) family, EGF and PDGF, and by a number of receptor-and nonreceptor-tyrosine kinases [12][13][14][15][16]. Stat3 was originally investigated as a molecule that was capable of selectively interacting with an enhancer element in the promoter of acute-phase response genes following stimulation by inteleukin-6 (IL-6) [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In the first case, the tyrosine phosphorylation is mediated by the tyrosine kinase activity of the stimulated IL-6 receptor complex (IL-6Ra/gp130/ JAK) (Schindler et al, 1995). In the other case, recent reports indicate that the serine phosphorylation is mediated by protein kinase C-delta, which in turn is activated by a signal transduction pathway consisting of Vav, Rac-1, MEKK and SEK-1 (Schuringa et al, 2000). In this study, we have shown that statins reduce IL-6-induced CRP expression via the inhibition of protein geranylgeranylation.…”
Section: Pleiotropic Effects Of Statins Target Crpmentioning
confidence: 96%